2021
DOI: 10.3390/diagnostics11061124
|View full text |Cite
|
Sign up to set email alerts
|

International HIV Dementia Scale for HIV-Associated Neurocognitive Disorders: A Systematic Review and Meta-Analysis

Abstract: The present study aims to systematically review the evidence on the accuracy of the International HIV Dementia Scale (IHDS) test for diagnosing human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND) and outline the quality and quantity of research evidence available on the accuracy of IHDS in people living with HIV. We conducted a systematic literature review, searching five databases from inception until July 2020. We extracted dichotomized positive and negative test results at various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…54 A recent systematic review found that the threshold of 10 is the most useful for optimal HAND screening (including ANI, symptomatic HAND, and HAD), with fair diagnostic accuracy. 57 For HAND screening, the test had a sensibility of 61.9% and a specificity of 67.5%. The sensibility was 61.8% for symptomatic HAND detection, but with a higher specificity of 73.6%.…”
Section: Screening For Cognitive Impairmentmentioning
confidence: 98%
“…54 A recent systematic review found that the threshold of 10 is the most useful for optimal HAND screening (including ANI, symptomatic HAND, and HAD), with fair diagnostic accuracy. 57 For HAND screening, the test had a sensibility of 61.9% and a specificity of 67.5%. The sensibility was 61.8% for symptomatic HAND detection, but with a higher specificity of 73.6%.…”
Section: Screening For Cognitive Impairmentmentioning
confidence: 98%
“…While cognitive assessment with MoCA showed no significant decline, the assessment with IHDS showed significant deficit, particularly in motor and psychomotor functioning, attributable to slow information processing speed as one of the most common cognitive impairments in HIV Associated Neurocognitive Disorder(HAND) (11). This suggests the specificity and strength of IHDS in screening for subcortical cognitive deficits, which are typical in HIV (12). Cognitive impairment (CI) in patients living with HIV is commonly reported.…”
Section: Discussionmentioning
confidence: 98%
“…The IHDS is the most common HIV-associated neurocognitive disorder (HAND) screening tool used in many African countries including South Africa, Uganda, and Cameroon ( 20 23 ). In addition, most recent systematic reviews and meta-analyses show that the IHDS has fair diagnostic accuracy in all forms of HAND (asymptomatic neurocognitive disorder, symptomatic neurocognitive, and HIV-associated dementia) ( 24 ). The presence of neurocognitive impairment was explained by the sum of a 3-item IHDS (timed finger tapping test, alternating hand sequence test, and memory-recall test) cutoff score of ≤ 10 in different studies ( 19 , 25 ).…”
Section: Methodsmentioning
confidence: 99%